Molecular detection of Leishmania infantum and Leishmania tropica in rodent species from endemic cutaneous leishmaniasis areas in Morocco - Echchakery, Mohamed (Parasit Vectors, 2017)
BACKGROUND: Leishmaniasis remains a major public health problem in African nations, including Morocco, where little is known about the vertebrate reservoirs involved in the causal parasites’ transmission cycles. The present study investigates the role of rodent species as potential reservoirs of Leishmania spp. in central Morocco, where both L. tropica and L. infantum have been reported. METHODS: Rodents were caught from 22 sites in central Morocco, by using Sherman metal traps, and identified morphologically. For each specimen, genomic DNA was extracted from different tissues using the Speed Tools DNA extraction Kit. Then, samples were PCR-analyzed, targeting the SSU rRNA gene to detect Leishmania spp. DNA, followed by amplification of the internal transcribed spacer 1 (ITS1) and its sequencing to identify the species. RESULTS: A total of 197 rodents belonging to ten species were captured and identified: Rattus rattus (40.61%), Mus musculus (25.38%), Apodemus sylvaticus (8.63%), Mus spretus (7.11%), Meriones shawi (5.58%), Rattus norvegicus (4.57%), Meriones libycus (3.05%), Mastomys erythroleucus (2.03%), Gerbillus campestris (2.03%) and Lemniscomys barbarus (1.01%). Molecular analysis revealed the presence of Leishmania species in 18 specimens: six R. rattus (out of 80 captured; 7.5%), 11 M. musculus (out of 50 captured; 22%), and one R. norvegicus (out of 9 captured; 11.11%). CONCLUSIONS: To the best of our knowledge, L. infantum and L. tropica were identified in rodent species for the first time in Morocco. These findings suggest that rodent species may be involved in L. infantum and L. tropica transmission cycles in this country but that further studies are needed to confirm their role as reservoirs of Leishmania species in Morocco. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13071-017-2398-8) contains supplementary material, which is available to authorized users.